Critical Appraisal of Economic Evaluation Studies (Part I): Types of Studies. Cost-Benefit Analysis - Azevedo, Luís Filipe; Sousa-Pinto, Bernardo (Journal of the Portuguese Society of Anesthesiology, 2019)
Economic evaluation studies are valuable and indispensable tools in the assessment of health technologies, taking into account (but not exclusively) their costs. In fact, there are different types of economic evaluation studies, which can be generally classified as partial or full economic evaluations. While partial economic evaluations solely aim to quantify costs, full economic evaluations take into account both costs and consequences (health outcomes and clinical effectiveness) of the assessed alternatives. This latter group of studies includes cost-benefit, cost-effectiveness, and cost-utility analysis, which differ in the approach used to express consequences. In cost-benefit studies, consequences and health outcomes are expressed in monetary units along with costs. This allows, for example, the assessment of whether the benefits (consequences or health gains as expressed in monetary units) of a given alternative are higher than its costs. While decision-makers may more easily interpret cost-benefit studies, the monetary valuation of health outcomes (such as gains in life years or in quality of life) is not without controversy – this valuation is typically based on the human capital, contingent valuation, or revealed preferences methods, each one with their own limitations.